Developing a Bilingual Guidebook for Desa Wisata Penglipuran Bali - Syahlaa Puspita Aliifah; Achmad Suyono (JLT Jurnal Linguistik Terapan, 2025)
Penglipuran Tourism Village is one of Bali’s tourism villages, which offers natural beauty and cultural heritage. In 2023, it was awarded as the best tourism village by UNWTO. However, the lack of tourist information became an issue, so the researcher developed a bilingual guidebook to provide additional information for tourists. The research applied Design and Development Research (DDR) with the ADDIE model: Analysis, Design, Development, Implementation, and Evaluation. The data was collected through observation, interviews, and documentation. The final product was an 88-page bilingual guidebook in Indonesian and English, validated by experts and tested by 55 respondents, gaining an average score of 4.68/5. The guidebook contains history, general information, travel tips, fun facts, tourist attractions, activities, facilities, cultural arts, accommodations, local products, and tour packages. It is expected to help tourists explore Penglipuran Village and serve as a promotional tool for local and international visitors.